Marcel Broodthaers (ed. Walker Art Center Minneapolis 1989). - Compton, Michael; Crimp, Douglas; Goldwater, Marge; Jenkins, Bruce; Mosebach, Martin; Exhibition. Marcel Broodthaers (3.1). Exhibition. Marcel Broodthaers (3.2). Exhibition. Marcel Broodthaers (3.3). Exhibition. Marcel Broodthaers (3.4). Brussel. Los Angeles. Minneapolis. Pittsburgh. Bozar - Paleis voor Schone Kunsten Brussel. LACMA (Los Angeles County Museum of Art) Los Angeles. Museum of Art Carnegie Institute Pittsburgh. Walker Art Center Minneapolis. Walker Art Center Minneapolis. 1989-04-09. 1989-07-09. 1990-01-20. 1990-04-15. 1989-06-18. 1989-10-22. 1990-03-18. 1990-06-24 (Minneapolis : Rizzoli International Publications New York Walker Art Center Minneapolis, 1989)
This exhibition and book are intended to provide an overview of Broodthaers's life and work, and constitute the first opportunity for an American audience to examine in depth the oeuvre of one of Europe's most prominent postwar artists. The catalogue features over 250 illustrations, many in color, of works from all phases of Broodthaers's career, including the first comprehensive photographic documentation of his museum Fictions, and accompanies an internationally circulating exhibition in association with the Palais des Beaux-Arts Brussels.
+ 1 dubbel zie speciale kast
ind. tent. p. 210-213, The Museum and The Décors p. 214, gr. tent. p. 215-217, filmog. p. 218-220, bibliog. p. 221
Engels
boek
Keywords: Broodthaers, Marcel